2014
DOI: 10.1371/journal.pone.0099242
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Reactive Oxygen Species by Deregulation of ARNT Enhances Chemotherapeutic Drug-Induced Cancer Cell Death

Abstract: BackgroundUnique characteristics of tumor microenvironments can be used as targets of cancer therapy. The aryl hydrocarbon receptor nuclear translocator (ARNT) is an important mediator of tumor progression. However, the functional role of ARNT in chemotherapeutic drug-treated cancer remains unclear.Methodology/Principal FindingsHere, we found that knockdown of ARNT in cancer cells reduced the proliferation rate and the transformation ability of those cells. Moreover, cisplatin-induced cell apoptosis was enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Under normoxic conditions, ARNT, also known as HIF‐1β, serves as a dimerization partner for several transcription factors, including MDR1, thereby contributing to tumorigenesis and drug resistance . The results of this study show that ARNT expression in CDDP‐resistant GC cells and tissues was higher than that in GC cells and tissues.…”
Section: Discussionmentioning
confidence: 69%
“…Under normoxic conditions, ARNT, also known as HIF‐1β, serves as a dimerization partner for several transcription factors, including MDR1, thereby contributing to tumorigenesis and drug resistance . The results of this study show that ARNT expression in CDDP‐resistant GC cells and tissues was higher than that in GC cells and tissues.…”
Section: Discussionmentioning
confidence: 69%
“…We previously found that 4βHWE selectively killed oral cancer cells but the role of oxidative stress was not addressed. NAC, a free radical scavenger, has been frequently used to investigate the drug‐induced oxidative stress effect . In Figure A, the decrease of cell viability in 4βHWE‐treated oral cancer (Ca9–22) cells were significantly rescued by NAC pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…NAC, a free radical scavenger, has been frequently used to investigate the drug-induced oxidative stress effect. [29][30][31][32] In Figure 1A, the decrease of cell viability in 4bHWE-treated oral cancer (Ca9-22) cells were significantly rescued by NAC pretreatment. In Figure 1B, the slightly decreased cell viability of 4bHWE-treated oral normal cells (HGF-1) was also rescued with slightly improved proliferation.…”
Section: Assessment Of Cell Viability Of 4bhwe-treated Oral Cancer mentioning
confidence: 96%
“…By the addition of ROS scavenger NAC to experiments, the role of EANA‐induced oxidative stress on cell viability was clarified . Figure B shows that NAC pretreatment significantly increases the cell viability of all EANA treatments in oral cancer cells than EANA alone ( P < .05‐.0001), whereas the cell viability of oral normal cells (HGF‐1) maintains healthy regardless of NAC pretreatment.…”
Section: Resultsmentioning
confidence: 99%